The Influence of Financial Literacy, Financial Inclusion, Hedonistic Lifestyle, and Peer Groups on the Personal Financial Behavior of Management Students at the Faculty of Economics and Business, University of Mataram - Sa’adatallayyali Sa’adatallayyali; Burhanudin Burhanudin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the influence of financial literacy, financial inclusion, hedonistic lifestyle, and peer groups on the personal financial behavior of Management students at the Faculty of Economics and Business, University of Mataram. The research applied a quantitative approach with an associative design involving 170 respondents selected through purposive sampling. Data were collected using structured questionnaires distributed through online platforms and analyzed using Structural Equation Modeling based on Partial Least Squares with SmartPLS 4 software. The findings indicate that financial literacy positively influences personal financial behavior by strengthening financial competence, rational decision making, and financial control. Financial inclusion also demonstrates a positive effect through improved access to formal financial services and digital financial ecosystems. Hedonistic lifestyle negatively affects personal financial behavior because pleasure oriented consumption tendencies encourage impulsive spending and weaken financial discipline. Peer groups exert the strongest positive influence by shaping behavioral adaptation, financial habits, and social norms related to money management. The study confirms that students’ financial behavior is simultaneously influenced by cognitive, social, and behavioral dimensions within contemporary university environments.